The Frequency of Raised Liver Enzyme in Patients on Anti-Tuberculosis Drugs: Raised Liver Enzymes in Anti-Tuberculosis Therapy - Abdullah, Tariq; Khalid, Abdul; Mumtaz, Mehwish; Hamdani, Mazhar; Shahid, Muhammad Ali (Pakistan Journal of Health Sciences, 2026)
Anti-tuberculosis therapy is associated with hepatotoxicity, which may manifest as elevation of liver enzymes and can affect treatment adherence and outcome. Objective: To determine the frequency of raised liver enzymes in patients receiving anti-tuberculosis therapy. Methods: This prospective observational study was conducted at the Department of Medicine, AIMS Muzaffarabad, from May 2025 to December 2025. A total of 200 patients aged 18 to 70 years with pulmonary tuberculosis were enrolled through consecutive non-probability sampling. Patients with pre-existing liver disease, viral hepatitis, HIV, pregnancy, alcohol use, or concurrent hepatotoxic medications were excluded. All patients received standard first-line anti-tuberculosis therapy. Liver function tests were performed at baseline, 2 weeks, 4 weeks, 2 months, 4 months, and 6 months. Data were analyzed using SPSS version 30. Results:The mean age was 44.17 ± 15.55 years, and 59% were male. Elevated ALT was observed in 29.0%, AST in 39.0%, and ALP in 7.0% patients. Overall, hepatotoxicity was observed in 57% patients. Elevated enzyme concentration was more common among subjects aged over 50 and subjects with a BMI over 25 kg/m²; nevertheless, no statistical significance was reached for these observations. The levels of enzymes significantly increased during the follow-up periods (p<0.001). Conclusion: Antitubercular therapy is commonly associated with a considerable frequency of raised liver enzymes, emphasizing the need for proper monitoring in antitubercular therapy.